1985
DOI: 10.1111/j.1469-8749.1985.tb03768.x
|View full text |Cite
|
Sign up to set email alerts
|

EARLY DEVELOPMENT OF LOCOMOTION: SIGNIFICANCE OF PREMATURITY, CEREBRAL PALSY and SEX

Abstract: SUMMARY Data on the development of locomotion during the first two years of life were collected for 128 preterm infants (21 with varying degrees of cerebral palsy) and for 111 healthy term infants. Most stages of locomotion occurred at slightly later ages among the neurologically unimpaired preterm infants than among those born at term (age corrected for prematurity). There was no difference between preterm and term infants with regard to the number and types of pathways of locomotion, or to age at onset and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
23
0
4

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(33 citation statements)
references
References 22 publications
6
23
0
4
Order By: Relevance
“…Studies that compared walking onset ages between preterm infants without major neurological disabilities and normal full-term infants were inconclusive [9][10][11][12][13][14] . Some studies showed that preterm infants walk at older ages [10][11][12]14 , while others reported walking at similar ages as term infants 9,13 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that compared walking onset ages between preterm infants without major neurological disabilities and normal full-term infants were inconclusive [9][10][11][12][13][14] . Some studies showed that preterm infants walk at older ages [10][11][12]14 , while others reported walking at similar ages as term infants 9,13 .…”
mentioning
confidence: 99%
“…Some studies showed that preterm infants walk at older ages [10][11][12]14 , while others reported walking at similar ages as term infants 9,13 . Normal fullterm infants usually attain independent walking at about 12 months of age, and continuously refine their movement in the following years to establish a mature walking pattern 8,9,14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting multifarious primary networks enable the most appropriate circuitries to be selected. Indeed, ample variation characterizes the first phases of reaching and grasping behaviour 22,56,57 , of crawling [58][59][60] , of locomotor motility 21,41,61,62 , and of postural control 44,63,64 . The neural systems dedicated to a specific function explore, during the phase of primary variability, all motor possibilities available for that specific function.…”
Section: Primary Variabilitymentioning
confidence: 99%
“…Para crianças normais, acredita-se que por volta dos 7 anos os aspectos relativos à aquisição da marcha já apresentem semelhança com os do adulto (Vásquez, 2005). Já em indivíduos que possuam alguma enfermidades que afete o processo de maturação neurológica serão observados desvios no desenvolvimento (Caram, Funayama, Spina, Giuliani, & Neto, 2006;Largo, Molinari, Weber, Comenale, & Duc, 1985), porém isto não implicará na impossibilidade de adquirir habilidades necessárias para a deambulação, sendo observado que os portadores de enfermidades conseguem desenvolver a locomoção, embora isso ocorra de forma mais lenta que nos indivíduos normais (Mancini et al, 2002). Estudo realizado por Ferreira (2008) com portadores de PC do tipo hemiparético encontrou valores abaixo do esperado para os parâmetros de maturação de marcha, assim como os obtidos neste estudo.…”
Section: Quadro 2 Distribuição E Comparação Dos Parâmetros De Maturaçunclassified